HISTORICAL MANIFESTATION OF CULTURAL HARMONY BETWEEN UZBEK AND UKRAINIAN PEOPLES: THE CASE OF THE XASANOV FAMILY” (Scientific journal of the Fergana State University, 2026)
This article is dedicated to studying the life of the Khasanov family in Surkhandarya region, particularly in Sherobod district, as well as their cultural, social, and historical significance. The study analyzes the family history of Kholmurod Kholmurodovich and Yekaterina Gavrelyevna, their family values, the life paths of their children, and their labor activities in Sherobod, highlighting the cultural and ethnic harmony between the peoples of Surkhandarya and Ukraine.